Role of rodents in biological migration of 137Cs on fallows - V. A. Gaychenko (Ядерна фізика та енергетика)
Features of 137Cs accumulation by rodents and it migration in the pasture type food chains, and trophic char-acteristics, spatial distribution, the animals influence on the grass cover of different types biocenoses were stud-ied. The data of the radionuclides biogenic migration intensity are presented. The correlation of gray voles life and 137Cs localization in their colonies are shown.